Structural changes of economies: Lithuania in the global context - Dudzevičiūtė, Gitana; Mačiulis, Alminas; Tvaronavičienė, Manuela (Technological and Economic Development of Economy, 2014)
Structural economic change theory focuses on the process through which economic structures have been transformed from traditional agriculture economy to more modern and industrially diverse manufacturing and service ones. The purpose of this paper is to detect the pattern of structural changes of the Lithuanian economy and to evaluate it in the global context. Structural economic statistics of the countries provide a view of a particular year delivered by indicator of the level of output in a considered sector of selected country’s economy. Research methodology is based on the classic three-sector model, which involves structural changes’ assessment methods and comparative analysis of statistical data on economic structures. The main findings reveal peculiarities of the structural change tendencies of the Lithuanian economy in the global context. First of all, the economies of selected countries are being analyzed from the point of view of three-sectoral divisions, such as agriculture, industry and services; the authors highlight the main tendencies of global economy taken by regions. After further in-depth analysis of the Lithuanian economic structural changes’ assessment in the context of the other countries (regions) has been carried out and new evidence on patterns of structural change has been provided, concluding remarks have been formulated. Authors provide insights about peculiarities of Lithuanian economy’s structural changes, which could potentially lead to respective policy implications, ultimately aiming acceleration of economic development.